2006
DOI: 10.1021/es0605725
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of European129I Releases Supported by129I Analysis in an Alpine Ice Core

Abstract: 129I in the European environment originates predominantly from the industrial nuclear fuel reprocessing plants Sellafield (Great Britain), Marcoule, and La Hague (both France). While reliable data on 129I releases from La Hague exist for the whole period of operation, less is known about the contributions from Sellafield and Marcoule. For those periods where no data are available, i.e., for the first 16 years of the Sellafield operation and for the first 3 decades of the Marcoule operation, we estimated releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 19 publications
4
62
2
Order By: Relevance
“…5). On the other hand, the estimated fallout from gaseous Reithmeier et al (2006), gaseous emissions from Sellafield (1951e1965), (4) gaseous emissions from Sellafield during 1966e1975 are estimated as 25% of the liquid emissions during the same period [20% of the total releases (Reithmeier et al, 2006)]. …”
Section: Discussionmentioning
confidence: 99%
“…5). On the other hand, the estimated fallout from gaseous Reithmeier et al (2006), gaseous emissions from Sellafield (1951e1965), (4) gaseous emissions from Sellafield during 1966e1975 are estimated as 25% of the liquid emissions during the same period [20% of the total releases (Reithmeier et al, 2006)]. …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that iodate is the dominant specie of iodine in soil solution under non-flooded oxidizing soil condition (85%), while under the flooded condition (anoxic); the dominant specie is iodide [78]. in terrestrial environment due to the nuclear weapons testing [26,35,77,[84][85][86][87][88][89][90][91].…”
Section: Speciation Of Iodine In Soil and Sedimentmentioning
confidence: 99%
“…doi:10. /j.gca.2009 129 I/I up to 10 À5 in surface waters of western New York) (Rao and Fehn, 1999;Oktay et al, 2000;Reithmeier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%